Encouraging Sustainability and Innovation: Green Banking Practices Growing in Indonesia - Misbakhul Khaer; Saiful Anwar (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2022)
This article examines developing green banking practices in Indonesia, intending to encourage sustainability and innovation in the banking sector. Green banking is an approach that integrates environmental and social factors in banking operations to reduce negative impacts on the environment and increase contribution to sustainable development. The method used is a library with a descriptive approach. The findings in this study indicate that green banking or environmentally friendly banking has a significant role in creating a clean and sustainable banking environment. By adopting green banking principles, banks can better manage environmental risks, increase environmentally friendly financing portfolios, and implement sustainable business practices. In addition to direct benefits such as reducing credit risk and improving asset quality, green banking can also potentially increase corporate value and bank reputation in the eyes of the public and investors. To encourage the implementation of green banking, banks in Indonesia need to comply with relevant regulations and continue to promote environmentally sound practices. Thus, green banking and green banking can become a potent symbol of ecological awareness worldwide.